if
![{xsin}^{3}+ {ycos}^{3} = sin \times cos {xsin}^{3}+ {ycos}^{3} = sin \times cos](https://tex.z-dn.net/?f=+%7Bxsin%7D%5E%7B3%7D%2B++%7Bycos%7D%5E%7B3%7D++%3D+sin+%5Ctimes+cos)
and
![xsin = ycos xsin = ycos](https://tex.z-dn.net/?f=xsin+%3D+ycos)
prove that
![{x}^{2 } + {y }^{2} = 1 {x}^{2 } + {y }^{2} = 1](https://tex.z-dn.net/?f=+%7Bx%7D%5E%7B2+%7D++%2B++%7By+%7D%5E%7B2%7D++%3D+1)
Answers
Answered by
1
Answer:
it is a bit lengthy solution ... but you can reduce steps , i made them because i don't know the right approach so i have to go with every step.
Attachments:
![](https://hi-static.z-dn.net/files/d87/4f0818da14a697e3aa14dc542e9f2480.jpg)
Similar questions